Improvement of the antioxidant potential: impact of drying and extraction techniques on polyphenols in Arbutus unedo L. leaf aqueous extract - Zemour, Kamel; Chouhim, Kadda Mohamed Amine; Labdelli, Amina; Mairif, Mohamed; Ardjane, Tedj Eddine Adda; Moussaoui, Badreddine; Zemour, Hafidh; Laafer, Mohammed (Future Science, 2024)
The search for alternatives to chemical pharmaceutical products remains an urgent and crucial step for humanity. In this regard, the use of plants presents an ideal approach for such biological studies. Arbutus unedo L., which belongs to the family Ericaceae, is one of the species that holds significant importance in traditional pharmaceutical uses. In Algeria, the use of this species in traditional treatment is generally rare. Therefore, this study aims to highlight its medicinal importance and the proper method for extracting its bioactive elements. To achieve this, the biological activity of leaves including total phenolic content (TPC), DPPH assay, and total flavonoid content (TFC), were assessed under four different drying temperatures (shade-drying, sun-drying, 40°C and 60C°) and two extraction methods after maceration (centrifugation, filtration). The results have indicated that these processes have affected the final accumulation of polyphenols and antioxidant activity in the leaf extracts. Additionally, it has been highlighted that the centrifugation method extracts a higher biochemical amount, especially after drying at 40°C. Furthermore, Arbutus unedo L. leaves should be considered a promising source of natural compounds to be used as ingredients in various fields.